Idiopathic orbital inflammation (orbital inflammatory pseudotumour): an unusual cause of transient ischaemic attack. Issue 1 (January 1995) - Borruat, F X; Vuilleumier, P; Ducrey, N; Fankhauser, H; Janzer, R C; Regli, F
Abstract : A patient with idiopathic inflammation of the right orbit, established by biopsy, developed episodes of transient left sensorimotor hemiparesis. Neuroimaging showed intracranial extension of the disease with pronounced narrowing of the right internal carotid artery in its intracavernous portion. Oral cyclophosphamide induced gradual improvement. Transient ischaemic attack is rarely found in association with orbital disease and indicates possible intracranial extension.